(untitled) (Scientific journal of the Fergana State University, 2025)
The direction of linguoculturology is associated with the linguistic landscape of the world formed in any culture. The national cultural code is active in proverbs and sayings, embodying various spheres of human life and stored in the collective memory. While the figurative representation of concepts and their transmission through symbols is studied within the framework of semiotics, cultural codes are the object of research of linguoculturology. In the study, euphemisms within proverbs and sayings are activated through various codes, and the following cultural codes were distinguished: zoomorphic, biomorphic, animic, gastronomic, anthropomorphic, historical, religious, mythological, subject, and time code. The article analyzed zoomorphic, subject and gastronomic cultural codes based on proverbs and sayings divided into thematic groups.